Photocatalytic Degradation Of Indigo Carmine And Phenol Using Agzs04-Deposited Zno Under Outdoor Light Irradiation - Choo, Hui Sun (2014)
Silver sulfate (Ag2S04) was successfully deposited on ZnO via a simple impregnation method. The as-synthesized sample was characterized by XRD, SEM, TEM, EDX, FTIR, UV-vis DRS and BET surface characteristic. Then, the photocatalytic activities of pure ZnO and three Ag2S04-deposited ZnO with different Ag2S04 loading were being evaluated for the degradation of indigo carmine and phenol under outdoor light irradiation. Results showed that the photocatalytic activities of all theer Ag2S04-deposited ZnO were higher than pure ZnO and commercial Ti02 for both pollutants degradation, especially 0.03 Ag2S04/ZnO which exhibited superior photocatalytic performance compare to others. After that, calcination temperature at 300 oe was found to be the most suitable condition for the preparation of 0.03 Ag2S0